Low Expression in Xenopus Oocytes and Unusual Functional Properties of α1β2γ2 GABAA Receptors with Non-Conventional Subunit Arrangement. - Roland Baur; Erwin Sigel (PLoS ONE, 2017)
The major subunit isoform of GABAA receptors is α1β2γ2. The subunits are thought to surround an ion pore with the counterclockwise arrangement α1γ2β2α1β2 as seen from the outside of the neuron. These receptors have two agonist sites and one high affinity drug binding site specific for benzodiazepines. Recently, this receptor was postulated to assume alternative subunit stoichiometries and arrangements resulting in only one agonist site and one or even two sites for benzodiazepines. In order to force a defined subunit arrangement we expressed a combination of triple and dual concatenated subunits. Here we report that these unconventional receptors express only small current amplitudes in Xenopus oocytes. We determined agonist properties and modulation by diazepam of two of these receptors that resulted in currents large enough for a characterization, that is, β2-α1-γ2/α1-γ2 and β2-α1-γ2/β2-γ2. The first pentamer predicted to have two benzodiazepine binding sites shows similar response to diazepam as the standard receptor. As expected for both receptors with a single predicted agonist site the concentration response curves for GABA were characterized by a Hill coefficient < 1. β2-α1-γ2/β2-γ2 displayed a mM apparent GABA affinity for channel opening instead of the expected μM affinity. Based on their subunit and binding site stoichiometry, that contradicts all previous observations, their unusual functional properties and their very low expression levels in oocytes, we consider it unlikely that these unconventional receptors are expressed in neurons to an appreciable extent.